2012
DOI: 10.1007/s11892-012-0341-0
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Insulin Resistance in Youth with Type 2 Diabetes

Abstract: Type 2 diabetes (T2DM), historically an adult disease, is now increasingly prevalent in obese youth. Poor diet and increased sedentary behavior contribute to the increasing rates of obesity in youth, yet not all obese children develop T2DM. In general, T2DM is characterized by both insulin resistance (IR) and pancreatic beta-cell insufficiency. In children, IR is related to elevated body mass index (BMI) and pubertal hormones, along with abnormal fat partitioning, elevated free fatty acids, inflammation, and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 79 publications
3
59
0
Order By: Relevance
“…35 It has also been reported that in obese children, pancreatic β-cell insulin secretion may be unable to respond to the increased demands imposed by puberty, resulting in inadequate regulation of blood glucose levels. 36 We here suggest that this dysregulation may be augmented in children with the combined condition of central obesity and suboptimal-25(OH)D status. These 7 4 This work does not include data for the full sample of the primary (GOCS) study.…”
Section: Combined Effects Of Obesity and Suboptimal-25(oh)d On Ir At mentioning
confidence: 65%
“…35 It has also been reported that in obese children, pancreatic β-cell insulin secretion may be unable to respond to the increased demands imposed by puberty, resulting in inadequate regulation of blood glucose levels. 36 We here suggest that this dysregulation may be augmented in children with the combined condition of central obesity and suboptimal-25(OH)D status. These 7 4 This work does not include data for the full sample of the primary (GOCS) study.…”
Section: Combined Effects Of Obesity and Suboptimal-25(oh)d On Ir At mentioning
confidence: 65%
“…Adolescents with T2DM have impaired exercise capacity even when compared to obese controls without diabetes (23). Insulin resistance in T2DM has been thought to be related to a combination of excess lipid production and mitochondrial dysfunction (24,25). Obesity is associated with the presence of increased free © Translational Pediatrics.…”
Section: Physiology In Type 2 Diabetesmentioning
confidence: 99%
“…Excessive free fatty acid production also leads to an increase in reactive oxygen species, which affects mitochondrial function (24). The presence of reactive oxygen species also effects adequate insulin secretion from the beta-cells from the pancreas (24).…”
Section: Physiology In Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the pathophysiology of T2D in adolescents is similar to that of adults with insufficient insulin production from pancreatic beta-cells and insulin resistance, the comorbidities in young diabetes may be more aggressive than in adults [20]. Serious comorbidities are also seen earlier in the patient's life because of the longer duration of the T2D and uncontrolled blood glucose [21].…”
Section: Effects Of Comorbid Depression On T2dmentioning
confidence: 99%